2016
DOI: 10.1215/00127094-3167168
|View full text |Cite
|
Sign up to set email alerts
|

Wave front sets of reductive Lie group representations

Abstract: If G is a Lie group, H ⊂ G is a closed subgroup, and τ is a unitary representation of H, then the authors give a sufficient condition on ξ ∈ ig * to be in the wave front set of Ind G H τ . In the special case where τ is the trivial representation, this result was conjectured by Howe. If G is a real, reductive algebraic group and π is a unitary representation of G that is weakly contained in the regular representation, then the authors give a geometric description of WF(π) in terms of the direct integral decomp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(43 citation statements)
references
References 50 publications
3
40
0
Order By: Relevance
“…In this article, we are interested in relating WF(τ ) and WF(Ind In Theorem 1.1 of [HHO16], it is shown that WF(Ind This result is proven in Section 3. Observe…”
Section: The Wave Front Set Of An Induced Lie Group Representationmentioning
confidence: 94%
See 3 more Smart Citations
“…In this article, we are interested in relating WF(τ ) and WF(Ind In Theorem 1.1 of [HHO16], it is shown that WF(Ind This result is proven in Section 3. Observe…”
Section: The Wave Front Set Of An Induced Lie Group Representationmentioning
confidence: 94%
“…For instance, they play a fundamental role in the seminal series of papers [Kob94], [Kob98a], [Kob98b], which give necessary and sufficient conditions for discrete decomposability of Lie group representations. This is the third in a series of papers on wave front sets of Lie group representations [HHO16], [Har]. The ideas in this series are heavily influenced by the earlier work of Kobayashi. Acknowledgements: B. Harris is indebted to Hongyu He and GesturÓlafsson, his former postdoctoral advisers at Louisiana State University, for their support, encouragement, knowledge, and wisdom.…”
Section: Thenmentioning
confidence: 99%
See 2 more Smart Citations
“…Many variations have been devised: analytic wavefront set (see [69] and [70] for a recent comparison of various definitions), homogeneous wavefront set [71], Gabor wavefront set [72], global wavefront set [73,74], etc.…”
Section: More Definitions Of the Wavefront Setmentioning
confidence: 99%